Putting positive weight‐related conversations into practice: The pilot implementation of a Knowledge Translation Casebook. (1st March 2020) - Bonder, Revi; Provvidenza, Christine F.; Hubley, Darlene; McPherson, Amy C.
Abstract: Background: Healthcare professionals (HCPs) play an important role in discussing weight with children and their parents but report barriers such as lack of training and supports. These barriers are especially prevalent within specialized populations such as children with autism spectrum disorder (ASD). To address this, a Knowledge Translation Casebook on positive weight‐related conversations was developed by a research team at a Canadian paediatric hospital. The purpose of the current pre‐implementation pilot study was to explore initial acceptability and adoption of the Casebook into clinical settings. Methods: An interactive, multimodal education workshop was created to provide HCPs with knowledge and training on how to have positive weight‐related conversations with children and parents. Two workshops were conducted using the same curriculum but delivered either in‐person or online. Participants were drawn from a team of clinicians at a teaching hospital whose care focuses on medication management for clients with ASD and clinicians participating in a distance learning programme on best practice care for clients with ASD. Participants completed a demographic questionnaire, workshop evaluation, and a pre‐workshop and post‐workshop questionnaire. Descriptive statistics were used to summarize demographic, questionnaire, and survey data. Answers to open‐ended questions were analysed using content analysis. Results: Participants agreed that the workshop gave them a clear understanding of the Casebook's content and helped them easily navigate the Casebook. Based on raw scores, self‐efficacy in having weight‐related conversations seemed to increase from pre‐to post‐workshop, but reported weight‐management clinical practice scores did not change over time. However, the small sample precluded in‐depth statistical analysis. Conclusions: The Casebook was acceptable and appeared to increase self‐efficacy about having weight‐related conversations with children with ASD and parents. More robust implementation strategies are needed to foster the uptake of best practices in weight‐related conversations into clinical practice.